Experimental conditions shape in vitro formation of murine platelet-leukocyte aggregates - Trivigno, Silvia Maria Grazia; Assinger, Alice; Schrottmaier, Waltraud Cornelia (Frontiers in Immunology, 2025)
BackgroundPlatelets interact with leukocytes to fine-tune their functions, thus providing essential regulation of (patho-) physiologic immune responses in various diseases. Circulating platelet-leukocyte aggregates (PLAs) represent a sensitive biomarker to estimate disease severity both in patients and murine models. However, a limited understanding of the sensitivity of PLA measurements to methodological variables may undermine their accuracy and comparability.ObjectivesTo elucidate how blood draw techniques, anticoagulation, processing delay and assay temperature affect murine platelet-leukocyte interactions.MethodsMurine blood was obtained via retro-orbital, vena cava or cardiac puncture, anticoagulated with heparin, citrate or acid-citrate-dextrose (ACD) +/- recalcification and stored for 30-120 min before stimulation at room temperature or 37°C with adenosine diphosphate (ADP), cross-linked collagen-related peptide (CRP-XL) and protease-activated receptor 4-activating peptide (PAR4-AP). PLA formation and leukocyte activation were analyzed by flow cytometry.ResultsBasal PLAs were minimally affected by blood sampling and anticoagulant, though delayed processing significantly raised basal PLAs. Agonist-induced PLA formation was independent of anticoagulation, and sampling technique did not affect ADP- or PAR4-AP-induced PLA levels. However, CRP-XL sensitivity was elevated in blood obtained by cardiac puncture. Contrarily, both delayed processing and stimulation at 37°C impaired CRP-XL sensitivity, but augmented ADP and PAR4-AP responses. Regulation of leukocyte activation did not follow PLA patterns, with monocytes and neutrophils displaying distinct susceptibility to anticoagulation, storage and temperature.ConclusionsVariations in preparing murine blood samples exert distinct influences on platelet-leukocyte interactions in vitro, underlining the critical need for fastidious assay optimization to support data reproducibility and comparability.